2017
DOI: 10.1177/1359105317745965
|View full text |Cite
|
Sign up to set email alerts
|

“That little doorway where I could suddenly start shouting out”: Barriers and enablers to the disclosure of distressing voices

Abstract: Hearing distressing voices is a key feature of psychosis. The time between voice onset and disclosure may be crucial as voices can grow in complexity. This study investigated barriers and enablers to early voice disclosure. Interviews with 20 voice hearers underwent Thematic Analysis. Beliefs about the effect of disclosure on self and others acted as a barrier and enabler to voices being discussed. Voice hearing awareness should be increased amongst young people, the public and care services. To support earlie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…The first theme examined the practitioner role in starting a conversation about voices. This was not always a straightforward process due to the previously reported barriers experienced by service users (Bogen‐Johnston, de Visser, et al, ) and practitioners (Coffey & Hewitt, ; McMullan et al, ). Our findings suggested that even within a specialist service for the treatment of psychotic experiences, practitioners may not always feel comfortable about having these conversations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first theme examined the practitioner role in starting a conversation about voices. This was not always a straightforward process due to the previously reported barriers experienced by service users (Bogen‐Johnston, de Visser, et al, ) and practitioners (Coffey & Hewitt, ; McMullan et al, ). Our findings suggested that even within a specialist service for the treatment of psychotic experiences, practitioners may not always feel comfortable about having these conversations.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature suggests that many service users with a diagnosis of psychosis have limited access to formal therapeutic conversations about voice hearing experiences that are consistent with the evidence base (RCP, ). Therefore, the availability of informal conversations can play an important role in bridging the all‐or‐nothing gap, yet barriers to such conversations exist for service users (Bogen‐Johnston, de Visser, et al, ) and practitioners (Coffey & Hewitt, ; McMullan et al, ). This study extends our understanding of these barriers from the perspectives of practitioners working in an EIP Service where these informal conversations are expected to occur (NICE, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for several patients there was also a substantial time lag between first contact to the psychiatric service and disclosure. A study by Bogen-Johnston et al (2019) concluded that the delay to disclosure was linked to the feelings of embarrassment and shame. We also found that feelings of embarrassment and fear of rejection or shame were contributing to nondisclosure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the voice content itself can act to prevent disclosure (i.e., voices telling the patient not to say anything) ( Beavan and Read, 2010 ). Most often, people do not disclose their voice hearing experiences because of concerns about stigmatizing responses from family, friends, and the wider society ( Beavan et al, 2011 ; Mawson et al, 2011 ; Hazell et al, 2017b ; Bogen-Johnston et al, 2017 ). Even within mental health services, patients are concerned about the potential for stigma from clinicians ( Beavan et al, 2011 ), and the fear of stigma is likely to be reinforced by clinicians who feel it is inappropriate to encourage and initiate conversations about hearing voices ( Coffey and Hewitt, 2008 ).…”
Section: Does a Symptom-specific Approach Generate Additional Barriermentioning
confidence: 99%